Automobile technology, hydrogen and climate change: a long term modelling analysis. (23rd April 2007) - Turton, Hal; Barreto, Leonardo
The transitions in the global automobile sector in the 21st century are uncertain both in terms of technologies and energy carriers. A key driving force of technological change in the long term could be the need to mitigate GHG emissions. This paper examines the role of the passenger car sector in a GHG mitigation strategy and presents a scenario of the automobile technology choices when a price on greenhouse gas emissions is imposed on the global energy system. The analysis has been conducted with ERIS, a multiregional energy systems, 'bottom up' optimisation model that endogenises technology learning and allows a detailed technology representation, in addition to capturing competing demands for transportation fuels, including hydrogen. Our results provide some policy insights by illustrating the potential for hydrogen to contribute to climate change mitigation, but show that fuel cell cars are an option for climate policy only over the very long term.